2007
DOI: 10.4028/www.scientific.net/msf.537-538.345
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Primary Cast Structure and Distribution of Inclusions in a St52-3 Type Continuously Cast Steel Slab

Abstract: The macrosegregation is one of the most recurrent phenomena in continuous steel casting of slabs. It often impedes the further processing and has detrimental effect on the quality of rolled strip. The macrosegregation can be explained by the interpretation of unit steps of solidification in continuous casting slabs as well as on the basis of the interaction of the inclusions at the interface of solid and liquid phases. Development of solid shell and interaction between growing dendrites and MnS segregation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…However, as the particle pushing mechanism sets in for larger inclusions, their number density gradually increases away from the billet surface in the columnar region and attains a constant value in the equiaxed zone (particles within the equiaxed zone are supposed to be distributed uniformly in this model). A similar distribution trend of larger inclusions getting accumulated in the centre was also observed by Fehérvári et al [38] who reported the percentage of inclusions of multiple size ranges across the billet crosssection in a St52-3 type continuously cast steel slab.…”
Section: Inclusion Distributionsupporting
confidence: 74%
“…However, as the particle pushing mechanism sets in for larger inclusions, their number density gradually increases away from the billet surface in the columnar region and attains a constant value in the equiaxed zone (particles within the equiaxed zone are supposed to be distributed uniformly in this model). A similar distribution trend of larger inclusions getting accumulated in the centre was also observed by Fehérvári et al [38] who reported the percentage of inclusions of multiple size ranges across the billet crosssection in a St52-3 type continuously cast steel slab.…”
Section: Inclusion Distributionsupporting
confidence: 74%